2023
DOI: 10.3390/ijerph20043270
|View full text |Cite
|
Sign up to set email alerts
|

Association between Long-Term Ambient PM2.5 Exposure and under-5 Mortality: A Scoping Review

Abstract: Studies have established a link between exposure to fine particles (PM2.5) and mortality in infants and children. However, few studies have explored the association between post-birth exposure to PM2.5 and under-5 mortality. We conducted a scoping review to identify relevant epidemiological evidence on the association between post-birth ambient PM2.5 exposure and under-5 mortality. We searched PubMed and Web of Science for articles published between 1970 and the end of January 2022 that explicitly linked ambie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Fine particles are mostly formed by combustion processes such as motor vehicles, power plants, and wildfires. Ultrafine particles are produced by the nucleation of gas molecules or by fragmentation of larger particles; these PM can penetrate deep inside the lungs or surpass the lung barrier and enter the blood system, respectively, causing a wide range of illnesses; while their effects on human health are complex and not fully understood, several studies have suggested that exposure to the air microbiome and pollution can have adverse impacts on the respiratory system (impaired lung function, inflammation and oxidative stress in the airways and lung tissue, bronchial hyperreactivity and asthma, increased susceptibility to respiratory infections, increased risk of chronic obstructive pulmonary disease and lung cancer) [1,2], cardiovascular system (systemic inflammation, oxidative stress, altered blood pressure, heart rate variability, atherosclerosis promotion, thrombosis, impaired endothelial function and vascular reactivity, increased cardiac arrhythmias, ischemia, risk of stroke and myocardial infarction) [3][4][5][6], immune system (affecting the production and function of cytokines, chemokines, antibodies, and immune cells, influencing the activation and differentiation of T cells and B cells, enhancing or suppressing allergic responses and autoimmune diseases, altering the susceptibility to infectious agents and vaccines) [7], gut microbiota (dysbiosis, increasing intestinal permeability and inflammation, altering the production of short-chain fatty acids and other metabolites that regulate host metabolism and immunity) [8,9], a correlation with autism and brain inflammation diseases [10,11], and a general increase in risk of mortality [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Fine particles are mostly formed by combustion processes such as motor vehicles, power plants, and wildfires. Ultrafine particles are produced by the nucleation of gas molecules or by fragmentation of larger particles; these PM can penetrate deep inside the lungs or surpass the lung barrier and enter the blood system, respectively, causing a wide range of illnesses; while their effects on human health are complex and not fully understood, several studies have suggested that exposure to the air microbiome and pollution can have adverse impacts on the respiratory system (impaired lung function, inflammation and oxidative stress in the airways and lung tissue, bronchial hyperreactivity and asthma, increased susceptibility to respiratory infections, increased risk of chronic obstructive pulmonary disease and lung cancer) [1,2], cardiovascular system (systemic inflammation, oxidative stress, altered blood pressure, heart rate variability, atherosclerosis promotion, thrombosis, impaired endothelial function and vascular reactivity, increased cardiac arrhythmias, ischemia, risk of stroke and myocardial infarction) [3][4][5][6], immune system (affecting the production and function of cytokines, chemokines, antibodies, and immune cells, influencing the activation and differentiation of T cells and B cells, enhancing or suppressing allergic responses and autoimmune diseases, altering the susceptibility to infectious agents and vaccines) [7], gut microbiota (dysbiosis, increasing intestinal permeability and inflammation, altering the production of short-chain fatty acids and other metabolites that regulate host metabolism and immunity) [8,9], a correlation with autism and brain inflammation diseases [10,11], and a general increase in risk of mortality [12,13].…”
Section: Introductionmentioning
confidence: 99%